2012
DOI: 10.1111/j.1365-3156.2012.03048.x
|View full text |Cite
|
Sign up to set email alerts
|

Cohort monitoring of persons with hypertension: an illustrated example from a primary healthcare clinic for Palestine refugees in Jordan

Abstract: Abstractobjective Recording and reporting systems borrowed from the DOTS framework for tuberculosis control can be used to record, monitor and report on chronic disease. In a primary healthcare clinic run by UNRWA in Amman, Jordan, serving Palestine refugees with hypertension, we set out to illustrate the method of cohort reporting for persons with hypertension by presenting on quarterly and cumulative case finding, cumulative and 12-month analysis of cohort outcomes and to assess how these data may inform and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 16 publications
0
105
0
4
Order By: Relevance
“…Such reporting would also provide programme retention and attrition rates, important parameters that can be used to judge overall programme management quality. 20,21 The high loss to follow-up rates in our study made it impossible to assess the true outcomes of fi stula repair at the 3-and 6-month follow-up intervals. We are only aware of one other published study from Ethiopia that has reported on loss to follow-up Résultats : Au total, une réparation chirurgicale des fistules obstétri-cales a concerné 475 femmes.…”
Section: Discussionmentioning
confidence: 93%
“…Such reporting would also provide programme retention and attrition rates, important parameters that can be used to judge overall programme management quality. 20,21 The high loss to follow-up rates in our study made it impossible to assess the true outcomes of fi stula repair at the 3-and 6-month follow-up intervals. We are only aware of one other published study from Ethiopia that has reported on loss to follow-up Résultats : Au total, une réparation chirurgicale des fistules obstétri-cales a concerné 475 femmes.…”
Section: Discussionmentioning
confidence: 93%
“…First, it endorses the use of e-Health and cohort analysis for monitoring and managing patients with DM and hypertension, and adds to the growing body of literature supporting the use of this method in Jordan and other countries for NCDs. 19,20 Second, e-Health also enforces adherence to UNRWA technical guidelines, as it is impossible to move from the current to the next screening page without completing the requested assignments, and we feel that this is partly responsible for the excellent performance of disease control measurements seen in Q2 2013. Nevertheless, it needs to be asked whether PPBG is the best monitoring method or whether this could be replaced by glycated haemoglobin, which is more convenient and reliable as a measure of diabetes control, although more costly.…”
Section: Public Health Action Cohort Analysis For Patients With Diabementioning
confidence: 99%
“…Interestingly, less than 10% of patients had both hypertension and DM, much lower than has been found elsewhere. 16,17 This requires further investigation to determine whether patients with DM have their blood pressure measured regularly and vice versa. About a third of patients with asthma had a severe attack in Quarters 2 and 3, compatible with the season of the year when asthma attacks are more frequent in the country.…”
Section: Public Health Action Chronic Disease In Primary Care In Malamentioning
confidence: 99%
“…First, the quarterly and cumulative cohort system that we have set up for chronic disease care generally functioned well, and is similar to systems being implemented for DM and hypertension clinics in central hospitals in Malawi 13 and in primary health care centres in other countries such as Jordan. 16,17 In these other settings, cohort monitoring relies on an electronic system, as this is probably the only way to follow a cohort of patients with their programmatic and management outcomes that increases cumulatively month by month. Over time, the EMR will also allow a survival analysis of each particular cohort to assess the quality of disease control, the development of co-morbidities and the programmatic outcomes, as has been undertaken in Jordan.…”
Section: Public Health Action Chronic Disease In Primary Care In Malamentioning
confidence: 99%